Analisis Technology Acceptance Model (TAM) terhadap Penggunaan Fintech Peer To Peer (P2P) Lending sebagai Alternatif Pendanaan Modal Kerja UMKM Kuliner di Alun-alun Karanganyar - Debora Citra Kaloka; Edi Wibowo (Lembaga Pengembangan Kinerja Dosen, 2024)
The study aims to determine how much (1) the effect of perceived ease of use on perceived usefulness in P2P Lending for culinary MSMEs in Karanganyar town square, (2) the effect of perceived ease of use on trust in P2P Lending for culinary MSMEs in Karanganyar town square, (3) the effect of perceived usefulness on trust in P2P Lending for culinary MSMEs in Karanganyar town square, (4) the effect of trust on attitude toward using in P2P Lending for culinary MSMEs in Karanganyar town square, and (5) the effect of attitude toward using on behavioral intention to use P2P Lending for culinary MSMEs in Karanganyar town square. This research uses Technology Acceptance Model (TAM) research methods with a sample of 75 respondents. Data analysis techniques using PLS SEM which consist of outer model and inner model. The outer model consists of convergent validity test, discriminat validity test, undimensionalitas test, and reliability test. The inner model uses R- square, Q square, path coefficient, Goodness of Fit, and descriptive analysis. The result showed that (1) perceived ease of use has a significant effect on perceived usefulness in P2P Lending for culinary MSMEs in Karanganyar town square, (2) perceived ease of use has a significant effect on trust in P2P Lending for culinary MSMEs in Karanganyar town square, (3) perceived usefulness has a significant effect on trust in P2P Lending for culinary MSMEs in Karanganyar town square, (4) trust has a significant effect attitude toward using in P2P Lending for culinary MSMEs in Karanganyar town square, (5) attitude toward using has a significant effect on behavioral intention to use P2P Lending for culinary MSMEs in Karanganyar town square.